2010
DOI: 10.1111/j.1749-6632.2010.05680.x
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and sexuality: key issues in premature menopause and beyond

Abstract: Woman's sexuality encompasses sexual identity, sexual function, and sexual relationships. It is modulated throughout life by life and reproduction-related events, health, relationships, and sociocultural variables. The aging process and menopause are two potent contributors to female sexual dysfunction. The earlier the menopause, the more severe and complex the impact on sexuality is. The younger the woman, the less she realizes the different key goals of her life cycle (falling in love, having a satisfying se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 32 publications
(158 reference statements)
0
26
0
6
Order By: Relevance
“…75 Signs and symptoms of estrogen deficiency include vaginal thinning, dryness, loss of elasticity, as well as difficulty with sexual arousal, interest, and sexual pain. 76 In a study of women undergoing risk reducing BSO, oophorectomized women reported significantly more vaginal dryness and dyspareunia than did the control group, despite the use of HT after surgery, suggesting that changes in sexual functioning are sustained and not entirely reversed by HT following BSO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…75 Signs and symptoms of estrogen deficiency include vaginal thinning, dryness, loss of elasticity, as well as difficulty with sexual arousal, interest, and sexual pain. 76 In a study of women undergoing risk reducing BSO, oophorectomized women reported significantly more vaginal dryness and dyspareunia than did the control group, despite the use of HT after surgery, suggesting that changes in sexual functioning are sustained and not entirely reversed by HT following BSO.…”
Section: Resultsmentioning
confidence: 99%
“…77 Sexual dysfunction in women with early BSO is often multifactorial, related not just to the physiologic consequences of hormonal deprivation, but also to psychological aspects. 74, 75 …”
Section: Resultsmentioning
confidence: 99%
“…Cuando la libido es el problema, la Tibolona o los andrógenos transdérmicos ayudan mucho. Aunque, los problemas sexuales ameritan un abordaje psico-bio-sociosexual bajo contextos de cambios físicos, intrapersonales, interpersonales y sociales (30,31).…”
Section: Síntomas Genitourinarios Y Sexualesunclassified
“…). In patients with HL, sexual function is associated with POF (Schover , Graziottin , Millheiser et al . , Sturdee & Pines ) and psychological distress and changes in role and social functioning (Hordern , Roper et al .…”
Section: Introductionmentioning
confidence: 99%